Increased macrophage M2/M1 ratio is associated with intracranial aneurysm rupture - Stratilová, Mária Hundža; Koblížek, Miroslav; Štekláčová, Anna; Beneš, Vladimír; Sameš, Martin; Hejčl, Aleš; Zámečník, Josef (Acta neurochirurgica, 2023)
PURPOSE: Intracranial aneurysm (IA) rupture results in one of the most severe forms of stroke, with severe neurological sequelae. Inflammation appears to drive aneurysm formation and progression with macrophages playing a key role in this process. However, less is known about their involvement in aneurysm rupture. This study is aimed at demonstrating how relationship between the M1 (pro-inflammatory) and M2 (reparative) macrophage subtypes affect an aneurysm's structure resulting in its rupture. METHODS: Forty-one saccular aneurysm wall samples were collected during surgery including 13 ruptured and 28 unruptured aneurysm sacs. Structural changes were evaluated using histological staining. Macrophages in the aneurysm wall were quantified and defined as M1 and M2 using HLA-DR and CD163 antibodies. Aneurysm samples were divided into four groups according to the structural changes and the M2/1 ratio. Data were analyzed using the Mann-Whitney U test. RESULTS: This study has demonstrated an association between the severity of structural changes of an aneurysm with inflammatory cell infiltration within its wall and subsequent aneurysm rupture. More severe morphological changes and a significantly higher number of inflammatory cells were observed in ruptured IAs (p < 0.001). There was a prevalence of M2 macrophage subtypes within the wall of ruptured aneurysms (p < 0.001). A subgroup of unruptured IAs with morphological and inflammatory changes similar to ruptured IAs was observed. The common feature of this subgroup was the presence of an intraluminal thrombus. CONCLUSIONS: The degree of inflammatory cell infiltration associated with a shift in macrophage phenotype towards M2 macrophages could play an important role in structural changes of the aneurysm wall leading to its rupture.
Keywords: Subarachnoid hemorrhage; Aneurysm, Ruptured; prasklé aneurysma; zánět; Intracranial Aneurysm; lidé; trombóza; intrakraniální aneurysma; Brain aneurysm; Macrophage polarization; Thrombosis; Humans; Macrophages; Intracranial aneurysm; Inflammation; makrofágy